Bilateral counter movement jump, squat, and drop jump performances in deaf and normal-hearing volleyball players: a comparative study - Makaraci, Y.; Özer, Ö.; Soslu, R.; Uysal, A. (Journal of Exercise Rehabilitation, 2021)
Since deaf athletes do not have any physical deficiencies, it is known that they can easily participate in sports competitions if their communication problems are resolved. This study aimed to compare the performances of olympic deaf and elite normal-hearing volleyball players in different jumping test protocols. A total of 26 male volleyball players participated in the study, comprised of 12 olympic level deaf and 14 elite level normal-hearing. Following anthropometric measurements, athletes performed bilateral counter movement, squat and drop jump tests on a force plate. Each test was performed 3 times with maximal effort separated by 45 seconds of passive recovery and the mean of the three trials was selected for analysis. Independent Samples t-test was used to compare the differences in mean values of jumping test parameters between the groups. Normal-hearing athletes are observed to have significantly better scores than deaf athletes in all test protocols. Considering that the number of studies on athletic performance in deaf athletes is limited, it can be said that our study will contribute to researchers and coaches in respect of detecting a key ability in volleyball, such as jumping, in different jump protocols.